Surface chemistry of Ti6Al4V components fabricated using selective laser melting for biomedical applications - Vaithilingam, Jayasheelan; Prina, Elisabetta; Goodridge, Ruth D.; Hague, Richard J.M.; Edmondson, Steve; Rose, Felicity R.A.J.; Christie, Steven D.R. (Elsevier, 2016)
Selective laser melting (SLM) has previously been shown to be a viable method for fabricating biomedical implants; however, the surface chemistry of SLM fabricated parts is poorly understood. In this study, X-ray photoelectron spectroscopy (XPS) was used to determine the surface chemistries of (a) SLM as-fabricated (SLM-AF) Ti6Al4V and (b) SLM fabricated and mechanically polished (SLM-MP) Ti6Al4V samples and compared with (c) traditionally manufactured (forged) and mechanically polished Ti6Al4V samples. The SLM– AF surface was observed to be porous with an average surface roughness (Ra) of 17.6 ± 3.7 μm. The surface chemistry of the SLM-AF was significantly different to the FGD-MP surface with respect to elemental distribution and their existence on the outermost surface Sintered particles on the SLM-AF surface were observed to affect depth profiling of the sample due to a shadowing effect during argon ion sputtering. Surface heterogeneity was observed for all three surfaces; however, vanadium was witnessed only on the mechanically polished (SLM-MP and FGD-MP) surfaces. The direct and indirect 3T3 cell cytotoxicity studies revealed that the cells were viable on the SLM fabricated Ti6Al4V parts. The varied surface chemistry of the SLM-AF and SLM-MP did not influence the cell behaviour.